Homestay accommodation as care work: a case study of private accommodation for refugees from Ukraine in Switzerland - Eveline Ammann Dula; Gesine Fuchs (Frontiers in Sociology, 2025)
In this paper we conceptualize homestay accommodation as care, through the feminist lens of Joan C. Tronto’s seminal works on the subject, based on a qualitative and quantitative survey of Ukrainian refugees in Switzerland. We used Tronto’s definition of care as an analytical framework to analyze care providing, giving, and refusing as negotiation processes in the context of unequal power relations between hosts and refugees, but also between civil society and the state. We identified a practical dimension of care, seen through the way hosts take care of the wellbeing of refugees. This form of care requires a lot of planning, coordination and organization, but also emotional engagement. For hosts, this means a large mental load, feeling responsible and providing this support in addition to their regular work and family life. On the other hand, refugees are not only receiving care, but also providing care or refusing care for different reasons. These negotiations can lead to conflicts and are embedded in power relations between hosts and refugees. Hosts often took on tasks that should actually be the responsibility of the authorities. The provision of private accommodation for refugees can be seen as an act of civil society to support the authorities, thus improving their capacity to accommodate refugees, often in line with official migration policy by incorporating expectations regarding the integration of refugees. However, there were also cases in which the host criticized state policy and showed solidarity with the refugees. The care perspective allows us to analyze the power relations that permeate relationships between hosts and refugees. We argue that the dynamics of private accommodation reflects or confirms current power relations between refugees and the host, but also has the potential to shift power relations between the state and civil society—as persons offering homestay accommodation address conflicts about the provision of care at the institutional and political level. It is in this way that the transfer of responsibility from the state to civil society is being questioned. Private accommodation has therefore the capacity to build forms of solidarity between refugees and civil society, linked to different forms of care providing and care needs.